"What isn't in the files, isn't in the world": Understanding state ignorance of irregular migration in Germany and the United Kingdom. Issue 2 (13th April 2020) - Boswell, Christina; Badenhoop, Elisabeth
Abstract: While there is extensive literature on states and knowledge, there has been little focus on state ignorance: instances where states are identified as lacking knowledge relevant to addressing social problems. We present the first systematic analysis of how states perceive and respond to ignorance, developing a typology of responses (denial, resignation, and elucidation). We test and refine the typology through analyzing state ignorance of unauthorized migration in Germany and the UK, 1990–2006. Public authorities in both countries responded to ignorance through both denial and resignation. However, variations in control infrastructures and bureaucratic cultures meant that "resignation" took distinct forms. In the UK, pragmatism about the limitations of state capacity implied that officials were sanguine about their "ignorance, " with pressure emanating from external political scrutiny. In Germany, by contrast, officials faced an acute conflict between bureaucratic and legal norms of the rule of law, and constraints to enforcement. Both cases reveal profound state ambivalence about elucidating social problems over which they have limited control.